A novel method for assessing bladder‐related pain reveals the involvement of nerve growth factor in pain associated with cyclophosphamide‐induced chronic cystitis in mice. (29th March 2015) - Fujita, M.; Kasai, E.; Omachi, S.; Sakaguchi, G.; Shinohara, S.
Abstract: Background: Pain is a prominent feature of interstitial cystitis/painful bladder syndrome (IC/PBS), but the underlying mechanisms are not fully understood. There is a lack of well‐characterized research tools, such as pain evaluation methods and experimental animal models, for investigating non‐ulcerative cystitis. We developed a novel method for evaluating bladder pain in mice with cyclophosphamide (CYP)‐induced cystitis. Methods: Cystitis was produced by a single intraperitoneal injection of CYP (300 mg/kg) or repeated injections of CYP (150 mg/kg once daily for 4 days). Blunt stimulation with a cotton probe was applied to the abdominal region, and the thresholds for withdrawal responses were measured quantitatively using an anaesthesiometer. Results: The single injection of CYP provoked acute cystitis with severe bladder inflammation in mice. In these mice, we could detect an increased sensitivity to blunt stimulation, which was abolished by intravesical lidocaine. The stimulation induced phosphorylation of extracellular signal‐regulated kinases in bladder‐projecting sensory neurons. Chronic treatment with CYP produced persistent pain responses to the blunt stimulus. Although there were few signs of bladder inflammation in these mice, the concentration of nerve growth factor (NGF) was elevated in bladder tissue, and NGF antiserum inhibited the hypersensitivity. Conclusions: The blunt probe method is useful for evaluating bladder pain signalling in mice, and revealed the involvement of an NGF‐sensitive pain pathway in chronic cystitis pain. This assessment method may be useful for studying the pathophysiology of bladder pain and for developing therapeutic strategies for non‐ulcerative IC/PBS in patients.